Era Disintegrasi: Kebangkitan Dinasti-Dinasti Kecil dan Kondisi Peradaban Islam: Era disentegrasi, Dinasti-dinasti Kecil, Peradaban Islam. - Ahmad, Ahmad Diaz Syahrezyah Makmur; Amrullah; Ahmad Diaz Syahrezyah Makmur (FIHROS: Jurnal Sejarah dan Budaya, 2025)
This research discusses the Era of Disintegration in the history of Islamic civilization, marked by the emergence of small dynasties after the collapse of the great caliphate. This period was an important phase that changed the political, social, and economic dynamics in the Islamic world. The method used is library research, using widely available literature sources, such as books, journal articles, research reports, and other electronic documents from libraries or online databases. Data obtained from relevant journal sources on the heritage of Islamic civilization during the Disintegration period. Data from these sources will be critically analyzed to investigate the political and social transformations that occurred during the disintegration period. The discussion on the disintegration period reflects the great challenges faced by Islamic civilization in maintaining its identity and power amidst rapid and complex changes.